Automatic Water Dispenser for Human Consumption using Telematic Devices - Benítez, Paola (2020)
Pollution in the environment grows unsustainably as the years go by and human beings are the main actor in the climatic changes that take place on our planet. Many of the technological inventions that have been produced are made from ethylene and are the most polluting from their manufacturing process to their use, because it takes many years to decompose. The advancement of technology provides well-being for humanity, but in turn many of the inventions have a negative side due to their high polluting capacity on the planet. One of them is disposable plastic containers that are not recycled. Therefore, this work aims to design a prototype of water dispenser that allows reducing contamination by single-use plastics, thus helping to fight for a less polluted environment.